Closed‐Loop Recyclable and Extrusion Reprocessable Thermosets Enabled by Guanylthiourea Structure - Zhen Yu; Yanlin Liu; Xiangyu Zhou; Yajin Fang; Zhaobin Tang; Jin Zhu; Junping Zhang (Advanced Science)
Abstract Plastic recycling is a critical step toward improving waste management and achieving economic recycling. Here, a thermoset crosslinked by guanythiourea structure (GTUH network) is reported, that addresses the recycling issue of thermosets by serial hybridization of thiourea and guanidine urea. The dual dissociative dynamic exchange reaction of guanamine urea and thiourea, combined with non‐covalent hydrogen bonding interactions, endows the network with rapid relaxation ability. GTUH networks, in particular, can be recycled through continuous extrusion processing due to multiple reversible mechanisms, as opposed to hot pressing alone. Even if reprocessed by hot pressing, only 5 min at 140 °C and 10 MPa are required. The oxidation enhancement mechanism of thiourea contributes to maintaining or even improving the mechanical properties of the recycled network. Moreover, the dynamic reactions of guanythiourea structure allow for closed‐loop chemical recycling of the network. Research into recyclable carbon fiber‐reinforced composites indicates promising potential applications for this material in the circular economy and resources.